Relationship between primary stroke center volume and time to endovascular thrombectomy in acute ischemic stroke. (23rd September 2021) - van Meenen, Laura C. C.; den Hartog, Sanne J.; Groot, Adrien E.; Emmer, Bart J.; Smeekes, Martin D.; Siegers, Arjen; Kommer, Geert Jan; Majoie, Charles B. L. M.; Roos, Yvo B. W. E. M.; van Es, Adriaan C. G. M.; Dippel, Diederik W.; van der Worp, H. Bart; et al.
Abstract: Background and purpose: We investigated whether the annual volume of patients with acute ischemic stroke referred from a primary stroke center (PSC) for endovascular treatment (EVT) is associated with treatment times and functional outcome. Methods: We used data from the Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands (MR CLEAN) registry (2014–2017). We included patients with acute ischemic stroke of the anterior circulation who were transferred from a PSC to a comprehensive stroke center (CSC) for EVT. We examined the association between EVT referral volume of PSCs and treatment times and functional outcome using multivariable regression modeling. The main outcomes were time from arrival at the PSC to groin puncture (PSC‐door‐to‐groin time), adjusted for estimated ambulance travel times, time from arrival at the CSC to groin puncture (CSC‐door‐to‐groin time), and modified Rankin Scale (mRS) score at 90 days after stroke. Results: Of the 3637 patients in the registry, 1541 patients (42%) from 65 PSCs were included. Mean age was 71 years (SD ± 13.3), median National Institutes of Health Stroke Scale score was 16 (interquartile range [IQR]: 12–19), and median time from stroke onset to arrival at the PSC was 53 min (IQR: 38–90). Eighty‐three percent had received intravenous thrombolysis. EVT referral volume was not associated with PSC‐door‐to‐groin time (adjusted coefficient: −0.49 min/annual referral, 95% confidence interval [CI]: −1.27 to 0.29), CSC‐door‐to‐groin time (adjusted coefficient: −0.34 min/annual referral, 95% CI: −0.69 to 0.01) or 90‐day mRS score (adjusted common odds ratio: 0.99, 95% CI: 0.96–1.01). Conclusions: In patients transferred from a PSC for EVT, higher PSC volumes do not seem to translate into better workflow metrics or patient outcome. Abstract : We investigated whether the annual volume of patients with acute ischemic stroke referred from a primary stroke center (PSC) for endovascular treatment (EVT) is associated with treatment times and functional outcome using multivariable regression modeling. We included 1541 patients from 65 PSCs. EVT referral volume was not associated with PSC‐door‐to‐groin time (adjusted coefficient: −0.49 min/annual referral, 95% confidence interval [CI]: −1.27 to 0.29) or 90‐day modified Rankin Scale score (adjusted common odds ratio: 0.99, 95% CI: 0.96–1.01).